(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article explores the spread and significance of the Naqshbandi Sufi tariqa in Central Asia, particularly among the Kyrgyz people. Sufism (tasawwuf) is presented as a distinct spiritual-religious movement within Islam, aimed at inner purification, moral development, and drawing closer to the Divine through spiritual practice. Special attention is given to the figure of Bahauddin Naqshband, known in Kyrgyz folk belief as Baabedin, who is revered as a saint and intermediary between people and Allah. Through his image and teachings, the Naqshbandi tariqa became deeply embedded in popular culture and religious practice. The phenomenon of syncretism – the blending of Islamic doctrines with pre-Islamic beliefs – is particularly emphasized. This is reflected in rituals, symbolism, folklore, and the epic Manas. In conclusion, the Naqshbandi tariqa played a significant role not only in the spiritual life of the region but also in shaping its cultural heritage.